PENERAPAN PROGRAM LAYANAN PENSIUNAN MELALUI KERJA SAMA PT. POS INDONESIA DAN KOPERASI NUSANTARA (KOPNUS) DI SURABAYA - Pramesti, Tia Ardhela; Pertiwi, Tri Kartika (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The retiree services program represents a strategic collaboration between PT. Pos Indonesia and Koperasi Nusantara (KOPNUS) aimed at expanding alternative channels for pension fund distribution in Indonesia. This community engagement research sought to implement and evaluate the effectiveness of the retiree services program through a direct approach to prospective service users. The activities were conducted in the Surabaya region, utilizing a method of direct visits to retirees' residences to offer a transfer of pension fund services from Bank BTPN to PT. Pos Indonesia offices. These visits also served to verify the retirees' status (whether they were still living, deceased, or had moved domiciles) and to explain the possibility of debt guarantees by KOPNUS. However, the results of the activities indicated that no retirees were willing to switch from Bank BTPN services. They felt they had already achieved comfort and trust in the service system they were currently using. This finding underscores the importance of a more adaptive outreach strategy and a deeper understanding of retirees' perceptions and emotional needs in public services.